ON POINT : a coachs game plan for life, leadership, and performing with grace under fire. - BORTON, PAM
ON Point gives you a seat on the bench with one of the nation's top women's basketball coaches. Distilling a 27-year coaching career into crucial lessons, ON Point drives home the essence of effective leadership under pressure, stress and times of chaos. ON Point delivers the practical knowledge and skills leaders need to achieve success in life and business, using stories from business, the courts, locker rooms, and press conferences. From leading a Big 10 basketball program to coaching high-performing teams in business, leader-focused chapters provide a holistic view of attributes crucial for ON Point leadership. -- Publisher.